Takedown : inside the hunt for Al Qaeda - Mudd, Philip (EBL-Schweitzer, 2013)
On September 11, 2001, as Central Intelligence Agency analyst Philip Mudd rushed out of the Eisenhower Executive Office Building next to the White House, he could not anticipate how far the terror unleashed that day would change the world of intelligence and his life as a CIA officer.